2019
DOI: 10.1111/jpc.14436
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of respiratory disease in Australian infants despite low rate of maternal cigarette smoking

Abstract: Aim The burden of wheezing illnesses in Australian infants has not been documented since the success of initiatives to reduce maternal cigarette smoking. We aimed to determine the incidence of wheeze and related health‐care utilisation during the first year of life among a contemporary Australian birth cohort. Methods A birth cohort of 1074 infants was assembled between 2010 and 2013. Parents completed questionnaires periodically. Several non‐exclusive infant respiratory disease phenotypes were defined, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…Prior studies have found that boys are at higher risk for developing wheezes than girls 41 . Our results also showed that the male sex is an associated factor of wheeze.…”
Section: Discussionsupporting
confidence: 81%
“…Prior studies have found that boys are at higher risk for developing wheezes than girls 41 . Our results also showed that the male sex is an associated factor of wheeze.…”
Section: Discussionsupporting
confidence: 81%
“…This may suggest that birth by caesarean section does not increase the incidence of infection but does increase the severity of infection, measured by hospitalisation. Very few infants in our cohort were exposed to tobacco smoke in the home, 13 and this homogeneity likely explains why we did not observe an association between passive smoke exposure and infection. We also did not find any evidence suggesting that the ALSPAC hygiene score, 14 measured at 12 months of life, was associated with incidence of infection.…”
Section: Discussionmentioning
confidence: 83%
“…We did not adjust for season as each child was followed for a complete year. We used inverse probability weighting to account for selection bias, as in previous studies of this cohort 8,13 . Regression models were reweighted to account for potential differential distribution of exposures between the inception cohort and non‐enrolled mothers.…”
Section: Methodsmentioning
confidence: 99%
“…Children may suffer from asthma morbidities due to exposure to environmental tobacco smoke or parental prenatal/postnatal smoking [ 42 ]. Although the rate of maternal cigarette smoking during pregnancy has decreased in the last decade in Australia [ 4 ], the evidence of the influence of smoking during pregnancy on childhood asthma persists [ 45 ]. However, few studies have investigated the number of cigarettes smoked during pregnancy and its effects on respiratory and allergic morbidities in their children [ 27 ].…”
Section: Discussionmentioning
confidence: 99%